2015
DOI: 10.1002/dev.21356
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to selective serotonin reuptake inhibitors (SSRI) increases aggression and modulates maternal behavior in offspring mice

Abstract: Selective serotonin reuptake inhibitors (SSRI) are commonly prescribed antidepressant drugs in pregnant women. SSRIs cross the placental barrier and affect serotonergic neurotransmission in the fetus. Although no gross SSRI-related teratogenic effects were reported, infants born following prenatal exposure to SSRIs are at higher risk for various developmental abnormalities. The aim of this study was to examine the effects of prenatal SSRI on social and maternal behavior in mice. To this end, pregnant female da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 59 publications
2
49
0
Order By: Relevance
“…Complementing our findings on distinct effects of maternal FLX on dominance, recent work showed prenatal maternal FLX treatment decreased aggressive behaviors, while treatment extending postnatally increased aggressive behaviors in adult C57BL/6 male offspring (Kiryanova, Meunier, Vecchiarelli, Hill, & Dyck, 2016). However, another report showed increased aggression in male offspring of ICR dams exposed to only prenatal FLX (Svirsky, Levy, & Avitsur, 2016). The discrepancies in aggression findings between these two studies may reflect strain x drug interactions.…”
Section: Discussionsupporting
confidence: 68%
“…Complementing our findings on distinct effects of maternal FLX on dominance, recent work showed prenatal maternal FLX treatment decreased aggressive behaviors, while treatment extending postnatally increased aggressive behaviors in adult C57BL/6 male offspring (Kiryanova, Meunier, Vecchiarelli, Hill, & Dyck, 2016). However, another report showed increased aggression in male offspring of ICR dams exposed to only prenatal FLX (Svirsky, Levy, & Avitsur, 2016). The discrepancies in aggression findings between these two studies may reflect strain x drug interactions.…”
Section: Discussionsupporting
confidence: 68%
“…Given the growing literature on the effects of serotonin on maternal care, it is perhaps not surprising that perinatal SSRIs alter maternal behavior in female offspring. However, to date only one study has been done in this area and findings from this work show that prenatal fluoxetine can reduce maternal behaviors of female offspring when they are mothers by reducing nest quality and delaying pup retrieval (Svirsky et al, 2016). Interestingly, these same prenatally R e v i s e d m a n u s c r i p t 16 SSRI-exposed female offspring showed more adaptability in maternal behaviors, with greater improvements in maternal care on postnatal day 2 and 3 than controls (Svirsky et al, 2016).…”
Section: Animal Models: Perinatal Ssris and Offspring Maternal Carementioning
confidence: 86%
“…In theory, antidepressant drugs can pass the placental barrier and directly affect brain development by altering neurotransmission . Several preclinical studies have shown that gestational exposure to antidepressants affects the development of neurotransmitter systems, resulting in long‐lasting effects on the behaviour of offspring . However, animal studies are not always generalisable to the clinical situation.…”
Section: Discussionmentioning
confidence: 99%